Can lesion volume and prostate-specific antigen density play a role in detecting clinically significant prostate cancer in Prostate Imaging Reporting and Data System-3 lesions on multiparametric magnetic resonance imaging? - Shashank Agrawal; Vishnu Prasad; Arun Ramadas Menon; Ginil Kumar Pooleri (Indian Journal of Urology)
Introduction: Recently, the Prostate Imaging Reporting and Data System – 3 lesions (PI-RADS 3) have been sub classified into “3a” - lesions with a volume of <0.5 mL and “3b” - lesions exceeding 0.5 mL, whereas the prostate-specific antigen density (PSAD) is an established adjunct tool for predicting clinically significant prostate cancer (csPCa). The objective of this study was to evaluate the association between the volume of PI-RADS 3 lesions and PSAD in diagnosing csPCa and to assess the sensitivity, specificity, negative predictive value (NPV), and positive predictive value (PPV) when PSAD is combined with the lesion volume. Methods: This retrospective single-center study reviewed the data of transperineal prostate biopsies performed under transrectal ultrasound guidance from January 2018 to December 2023. csPCa was defined as a Gleason score ≥3 + 4. Patients were divided into two groups based on the PIRADS-3 subclassification and PSAD. Results: Out of the 108 PIRADS-3 lesions, 17 patients had csPCa. All the patients with PIRADS-3a (n = 37) had clinically insignificant tumors or benign conditions. Receiver operating characteristic curve analysis for predicting csPCa showed that the (Area under the curve) AUC values of PSAD, prostate volume, and prostate-specific antigen were 0.899, 0.746, and 0.381, respectively. 16 csPCa patients in PIRADS-3b category had PSAD ≥0.29 ng/ml2, whereas 1 patient had PSAD <0.29 ng/ml2. Sensitivity, specificity, PPV, and NPV of PIRADS-3b lesions were 100%, 40.66%, 23.94%, and 100%, respectively, and it became 94.12%, 74.07%, 53.33%, and 97.56%, respectively, when PSAD was added to PIRADS-3b lesions. Conclusion: The combination of lesion volume of the PI-RADS 3 lesion and PSAD improved the PPV and specificity of detecting csPCa.